Oxidative damage of SP-D abolishes control of eosinophil extracellular DNA trap formation. Issue 1 (7th May 2018) - Yousefi, Shida; Sharma, Satish K; Stojkov, Darko; Germic, Nina; Aeschlimann, Salome; Ge, Moyar Q; Flayer, Cameron H; Larson, Erik D; Redai, Imre G; Zhang, Suhong; Koziol-White, Cynthia J; Karikó, Katalin; et al.
Abstract: The asthmatic airways are highly susceptible to inflammatory injury by air pollutants such as ozone (O3 ), characterized by enhanced activation of eosinophilic granulocytes and a failure of immune protective mechanisms. Eosinophil activation during asthma exacerbation contributes to the proinflammatory oxidative stress by high levels of nitric oxide (NO) production and extracellular DNA release. Surfactant protein-D (SP-D), an epithelial cell product of the airways, is a critical immune regulatory molecule with a multimeric structure susceptible to oxidative modifications. Using recombinant proteins and confocal imaging, we demonstrate here that SP-D directly bound to the membrane and inhibited extracellular DNA trap formation by human and murine eosinophils in a concentration and carbohydrate-dependent manner. Combined allergic airway sensitization and O3 exposure heightened eosinophilia and nos2 mRNA (iNOS) activation in the lung tissue and S-nitrosylation related de-oligomerisation of SP-D in the airways. In vitro reproduction of the iNOS action led to similar effects on SP-D. Importantly, S-nitrosylation abolished the ability of SP-D to block extracellular DNA trap formation. Thus, the homeostatic negative regulatory feedback between SP-D and eosinophils is destroyed by the NO-rich oxidative lung tissue environment in asthma exacerbations. Demonstration that specific carbohydrate-dependent inhibition of murine and human eosinophil extracellular DNA trap release is abolished by s-nitrosylation of the SP-D molecule.